Factors attributed to low birth weight in cities of Paraíba - Figueroa Pedraza, Dixis (Journal of Health Care, 2016)
Objectives: To analyze, in the time period from 1999 to 2007, factors associated with low birth weight(LBW) in liveborn infants of mothers living in the municipalities of Cabedelo and Cacimbas, in the Stateof Paraíba, Brazil. Method: Information from the Live Birth Information System (SINASC) was used.The differences in the population scale and in the Human Development Index were the main basis forchoosing the municipalities. Results: The municipalities had similar behaviors regarding discriminantfactors of weight at birth. In Cacimbas, as well as in Cabedelo, children from mothers who underwentless than six prenatal appointments and a pregnancy length from 22 to 36 weeks have shown a greater riskof LBW. In both municipalities, equally, multiparity has represented a protection related to the weightat birth. In the municipality of Cabedelo, children from mothers with age equal or superior to 35 yearshave shown a greater probability of LBW. Conclusion: In spite of the limited information available onSINASC, its usage has made it possible to identify factors that are common to LBW.